2022
DOI: 10.3390/ani12233354
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermal Manipulation on mRNA Regulation of Response Genes Regarding Improvement of Thermotolerance Adaptation in Chickens during Embryogenesis

Abstract: The phenomenon of increasing heat stress (HS) among animals is of particular significance when it is seen in economically significant industries, such as poultry. Due to the identification of the physiological, molecular, and genetic roots of HS responses in chickens, a substantial number of studies have focused on reducing the effects of HS in poultry through environmental management, dietary manipulation, and genetic alterations. Temperature manipulation (TM) during embryogenesis has been claimed to increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 90 publications
2
3
0
Order By: Relevance
“…Furthermore, the egg weight loss percentages for both studied groups were within the normal range, therefore egg weight loss did not impact embryo mortality and the hatchability percentages ( Tables 1 and 3 ). This finding is consistent with those previously mentioned by Ismail et al (2016) , El-Zeniny et al (2019) , Amjadian and Shahir (2020) , Saleh et al (2020) , and Ramiah et al (2022) .…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…Furthermore, the egg weight loss percentages for both studied groups were within the normal range, therefore egg weight loss did not impact embryo mortality and the hatchability percentages ( Tables 1 and 3 ). This finding is consistent with those previously mentioned by Ismail et al (2016) , El-Zeniny et al (2019) , Amjadian and Shahir (2020) , Saleh et al (2020) , and Ramiah et al (2022) .…”
Section: Discussionsupporting
confidence: 94%
“…Thermal manipulation during egg incubation is considered mild heat shock exposure during embryogenesis, which improves tissue stability, oxidative stress response, and immunological response to heat stress ( Al-Zghoul et al, 2023 ). Different thermal manipulation protocols resulted in a significant increase in heat shock proteins mRNA expression in the pectoral and thigh muscles ( Al-Zghoul et al, 2013 , 2015 ; Ali et al, 2022 ; Ramiah et al, 2022 ), and the same was associated with enhanced thermoregulation and thermotolerance, as previously reported by Al-Aqil and Zulkifli (2009) . Likewise, Li et al (2017) reported that thermal manipulation can promote mRNA and protein expression of growth marker genes and muscle-related genes.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations